2017
DOI: 10.1080/15476286.2017.1405211
|View full text |Cite
|
Sign up to set email alerts
|

G-Quadruplexes influence pri-microRNA processing

Abstract: RNA G-Quadruplexes (G4) have been shown to possess many biological functions, including the regulation of microRNA (miRNA) biogenesis and function. However, their impact on pri-miRNA processing remains unknown. We identified G4 located near the Drosha cleavage site in three distinct pri-miRNAs: pri-mir200c, pri-mir451a, and pri-mir497. The folding of the potential G4 motifs was determined in solution. Subsequently, mutations disrupting G4 folding led to important changes in the mature miRNAs levels in cells. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 48 publications
(55 reference statements)
4
51
0
Order By: Relevance
“…Indeed, we observed strong RBP binding at G4s for multiple published G4-binding proteins such as NONO, FUS, GRSF1, DROSHA, and DDX42 ( Fig. 5A and S6A) [40][41][42][43][44]. Additionally, many of the RBPs that exhibited the strongest G4-binding signal-PRPF4, GTF2F1, FAM120A, CSTF2T, and DDX6-have recently been shown to bind at putative G4 sites in mRNA UTRs [45].…”
Section: Cross-correlation Tracks Reproducibly Cluster Rbp Data Acrosmentioning
confidence: 75%
“…Indeed, we observed strong RBP binding at G4s for multiple published G4-binding proteins such as NONO, FUS, GRSF1, DROSHA, and DDX42 ( Fig. 5A and S6A) [40][41][42][43][44]. Additionally, many of the RBPs that exhibited the strongest G4-binding signal-PRPF4, GTF2F1, FAM120A, CSTF2T, and DDX6-have recently been shown to bind at putative G4 sites in mRNA UTRs [45].…”
Section: Cross-correlation Tracks Reproducibly Cluster Rbp Data Acrosmentioning
confidence: 75%
“…It has also been shown that rG4 has stronger binding affinity to Polycomb repressive complex 2 (PRC2) than unstructured Grich motif or duplex RNA (Wang et al 2017). Recently, it has been reported that rG4s have potential to form in primary and precursor microRNAs (Mirihana Arachchilage et al 2015;Kwok et al 2016b;Rouleau et al 2018), as well Canonical G-quadruplex (i.e., G3 L1-7) G3: G-tract sequences of 3 consecutive Gs L1-7: Loop sequences of 1-7 nucleotides : G-quartet : Guanine G-quadruplex thermostability: Figure 1. RNA G-quadruplex (rG4) structure.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Booy and colleagues also demonstrate that TERC nucleotides 11-28, which are included into terc-sRNA binding site (TERC 12-31) are folded into an internal G quadruplex which is responsible for P1 helix inhibition. Since it was shown that G4 RNA folding can be inhibited by using antisense oligonucleotide targeting the guanines involved in the G4 folding [106,107], we can speculate that binding of terc-sRNA and recruitment of AGO2 to TERC 5' region might act in collaboration with RHAU and prevent the formation of G4s, thereby favoring P1 helix formation. This hypothesis is also supported by the evidence that RHAU is also implicated in direct interactions with human AGO proteins [108,109].…”
Section: Terc-interacting Proteins: the Usual And Unusual Suspectsmentioning
confidence: 99%